2016
DOI: 10.1002/asi.23668
|View full text |Cite
|
Sign up to set email alerts
|

Shared values, new vision: Collaboration and communities of practice in virtual reference and SQA

Abstract: This investigation of new approaches to improving collaboration, user/librarian experiences, and sustainability for virtual reference services (VRS) reports findings from a grant project titled “Cyber Synergy: Seeking Sustainability between Virtual Reference and Social Q&A Sites” (Radford, Connaway, & Shah, –2014). In‐depth telephone interviews with 50 VRS librarians included questions on collaboration, referral practices, and attitudes toward Social Question and Answer (SQA) services using the Critical Incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
(57 reference statements)
0
4
0
1
Order By: Relevance
“…O ambiente atual, de rápida mudança tecnológica e orçamentos reduzidos, levarou os pesquisadores a observar que o desafio contínuo das VCoP é atender ao usuário de informações em formatos convenientes, a qualquer hora, em qualquer lugar (RANDFORD, 2017).…”
Section: Ideia Geralunclassified
“…O ambiente atual, de rápida mudança tecnológica e orçamentos reduzidos, levarou os pesquisadores a observar que o desafio contínuo das VCoP é atender ao usuário de informações em formatos convenientes, a qualquer hora, em qualquer lugar (RANDFORD, 2017).…”
Section: Ideia Geralunclassified
“…Finally, Radford et al and others have demonstrated that collaboration is vital for the provision of quality service and has the potential to be fostered between VRS librarians and those providing SQA services. 25…”
Section: Vrs Researchmentioning
confidence: 99%
“…The groups also collect cases. To achieve this, social networks such as communities of practice (COP) (Radford et al, 2017;Paasivaara and Lassenius, 2014) and process asset libraries (PAL) (Bayona-Or e et al, 2014;Lee et al, 2016) may be established to serve as a repository and stock of SPI knowledge, including characterized process implementations, tailoring policies, tailoring cases and so forth, and to help explain interpersonal SPI knowledge behaviors and increase mutual understandings in common or local language. This, in turn, can promote learning in SPI knowledge.…”
Section: Practical Implicationsmentioning
confidence: 99%